(untitled) (Discourse of Law and Administration, 2021)
The subject of the article is the analysis and assessment of the scope of criminalization of abandoning firearms or ammunition, which was defined in Art. 50 of the Act of May 21, 1999 on weapons and ammunition (Journal of Laws of 2020, item 955). First, attention was drawn to the lack of system consistency in the above-mentioned the scope and issues of proper interpretation of the concept of firearms. In the following parts of the article, an attempt was made to characterize the remaining features of the crime of abandoning firearms and ammunition in the aspect of criminalization limits set by the legislator. The last part of the article presents other circumstances relevant and irrelevant to the scope of criminal liability for the above-mentioned offense.